Deficiencies in technical and vocational education and training lecturer involvement qualifications and its implications in the development of work related skills - van der Bijl, A.; Oosthuizen, L.J. (South African Journal of Higher Education, 2019)
Technical Vocational Education and Training (TVET) lecturers play an important role in providing a competent workforce that can contribute to the economy in countries worldwide. The critical role played by TVET lecturers requires of them to have appropriate academic qualifications, workplace qualifications and experience, and teaching qualifications. Research has shown that few lecturers have adequate and required academic, workplace and teaching qualifications. The purpose of this study was to determine the deficiencies in TVET lecturer qualifications and how these deficiencies are addressed by management at TVET colleges in South Africa. While a substantial number of lecturers had academic qualifications at the time of investigation, deficiencies were found in TVET lecturers’ workplace qualifications and experience, as well as in their teaching qualifications. Having identified the deficiencies in TVET lecturer's qualifications, recommendations have been made to serve as guidelines in addressing the lack of either academic, teaching or workplace qualifications and experience.